2021
DOI: 10.1093/infdis/jiab228
|View full text |Cite
|
Sign up to set email alerts
|

Activating Killer-Cell Immunoglobulin-Like Receptors Are Associated With the Severity of Coronavirus Disease 2019

Abstract: Background Etiopathogenesis of the clinical variability of the coronavirus disease 2019 (COVID-19) remains mostly unknown. Here we investigate the role of Killer-cell Immunoglobulin-like receptor (KIR)/Human Leukocyte Antigen Class-I (HLA-I) interactions in the susceptibility and severity of COVID-19. Methods KIR and HLA-I genotyping and NK cell (NKc) receptors immunophenotyping in 201 symptomatic patients and 210 non-infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 48 publications
3
28
0
Order By: Relevance
“…Additionally, NK cell cytotoxic and secretory functions are tightly regulated by a dynamic balance between activating and inhibitory signals from an arsenal of membrane receptors, including killer cell immunoglobulin-like receptors (KIRs), randomly generated during NK cell differentiation and maturation ( Vidal et al, 2011 ). Specific KIR/ligand interactions seem to be associated with COVID-19 disease severity as demonstrated in a very recent paper ( Bernal et al, 2021 ) and by preliminary results from our ongoing study (unpublished observations).…”
Section: Innate Immunity: Natural Killer (Nk) Cellssupporting
confidence: 71%
“…Additionally, NK cell cytotoxic and secretory functions are tightly regulated by a dynamic balance between activating and inhibitory signals from an arsenal of membrane receptors, including killer cell immunoglobulin-like receptors (KIRs), randomly generated during NK cell differentiation and maturation ( Vidal et al, 2011 ). Specific KIR/ligand interactions seem to be associated with COVID-19 disease severity as demonstrated in a very recent paper ( Bernal et al, 2021 ) and by preliminary results from our ongoing study (unpublished observations).…”
Section: Innate Immunity: Natural Killer (Nk) Cellssupporting
confidence: 71%
“…Our study showed a direct correlation of the activating 2DS4 receptor with the plasma level of IFN-γ and IL6 in COVID-19 patients, biomarkers that are reported to be elevated during SARS-CoV-2 infection [25] in accordance with our study, although the production of these cytokines is systemic and can be partially attributed to the NK cell production. One recent study reported that the frequency of the 2DS4 gene was significantly increased in COVID-19 patients compared to controls [26].…”
Section: Discussionmentioning
confidence: 97%
“…Only five studies have investigated the impact of KIR receptors on SARS-CoV-2 infection ( Beksac et al, 2021 ; Bernal et al, 2021 ; Lesan et al, 2021 ; Littera et al, 2021 ; Hajeer et al, 2022 ). In contrast to our findings, a study with a small number of 16 patients from the German Caucasian cohort revealed that patients with activating KIR2DS5 were recovered from COVID-19 in a shorter time than the individuals negative for the KIR2DS5 gene ( Lesan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this study did not determine the frequencies of specific KIR and cognate HLA class I ligand combinations. Higher frequencies for KIR2DS4 in severe COVID-19 patients and KIR3DS1 + HLA-B*15:01 + in mild/moderate cases of COVID-19 than in control in Spanish indicate a potentially detrimental effect of activating KIR in COVID-19 ( Bernal et al, 2021 ). However, none of these genes and combinations were found to be significant in our study, probably because of the limited sample sizes in these other studies.…”
Section: Discussionmentioning
confidence: 99%